Accessibility of hypertensive users to health units and treatment adherence - Frota, Natasha Marques; Araújo, Thiago Moura de; Barros, Lívia Moreira; Caetano, Joselany Áfio; Santos, Zélia Maria de Sousa Araújo (Rev Rene, 2013)
We aimed to analyze the accessibility of hypertensive users to the health system with focus on treatment adherence. A cross-sectional study with quantitative approach was conducted in four Family Health Basic Units of Fortaleza-CE, Brazil. The sample consisted of 400 users. Data collection happened through a form applied from May to August 2011. About 97.5% of users were older than 40 years, and 67.2% were female. The accessibility to the referral service occurred in 47.2% of users to secondary care, of which 101 (25.2%) were referred to Emergency Units, and 88 (22.0%) were admitted to Inpatient Units. Most hypertensive patients adhered to healthy habits, except the use of dietetic sweeteners (36.0%) and physical exercise (35.0%). The hypertensive patients had good treatment adherence and difficulty in accessibility regarding counter-referral services to secondary and tertiary care services.DOI: https://doi.org/10.15253/2175-6783.2013000400009